Profile Analysis of Basic Science Process Skills for Students of SMP Negeri 2 Pagaralam Using the Test of Basic Process Skills - Hartono, Hartono; Ariska, Melly; Susanti, Rahmi (Jurnal Pendidikan MIPA, 2023)
Abstract: The purpose of this study was to describe the basic science process skills of the students of SMP Negeri 2 Pagaralam City. The study used a dominant-less dominant design with purposive sampling technique. The research was conducted at SMP Class VIII with a population of all class VIII students at SMP Negeri 2 Kota Pagaralam. The sample used was 18 students of class VIII at SMP Negeri 2 Pagaralam City. The results of the research conducted showed that: (1) grade VIII students at SMP Negeri 2 Pagaralam City on average had basic science process skills at a moderate level in solving questions using a valid instrument, namely the Test of Basic Process Skill (BAPS) as many as 36 questions. science process skills (2) student achievement for each indicator, namely observation by 65%, communication by 61%, clarification by 58%, measurement by 27%, prediction by 32%, and inference by 57%. Keywords: science process skills, test of basic process skills (BAPS) Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan keterampilan proses sains dasar siswa SMP Negeri 2 Pagaralam Kota. Penelitian ini menggunakan desain dominan-kurang dominan dengan teknik purposive sampling. Penelitian ini dilaksanakan di SMP Kelas VIII dengan populasi seluruh siswa kelas VIII SMP Negeri 2 Kota Pagaralam. Sampel yang digunakan adalah 18 siswa kelas VIII SMP Negeri 2 Kota Pagaralam. Hasil penelitian yang dilakukan menunjukkan bahwa: (1) siswa kelas VIII SMP Negeri 2 Kota Pagaralam rata-rata memiliki keterampilan proses sains dasar pada tingkat sedang dalam menyelesaikan soal dengan menggunakan instrumen yang valid yaitu Tes Keterampilan Proses Dasar (BAPS) sebanyak 36 pertanyaan. keterampilan proses sains (2) prestasi belajar siswa pada masing-masing indikator yaitu observasi sebesar 65%, komunikasi sebesar 61%, klarifikasi sebesar 58%, pengukuran sebesar 27%, prediksi sebesar 32%, dan inferensi sebesar 57%.  Kata kunci: keterampilan proses sains, tes keterampilan proses dasar (BAPS)DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp584-593